Analisis Kemampuan Berpikir Kritis Matematis Siswa Kelas VIII SMP Negeri 7 Ambon pada Materi Pola Bilangan - Arisandi, Aditia; Gerson Ratumanan, Tanwey; Molle, J. S. (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
This This research aims to describe the mathematical critical thinking abilities of class VIII students at SMP Negeri 7 Ambon on number patterns material. Type of research, namely qualitative and quantitative. The subjects in this research were 3 students selected from 25 students using the assessment criteria for number pattern test questions (high, medium and low) and the opinion of the subject teacher. Quantitative data analysis is used, namely calculating test results and then classifying them into benchmark assessments, while qualitative data consists of data reduction, data presentation and drawing conclusions. The results of this research show that CMH subjects fulfill 4 critical thinking indicators, namely interpretation, analysis, evaluation and inference, JID subjects fulfill three critical thinking indicators, namely interpretation, analysis and inference, MJ subjects can only fulfill interpretation and inference indicators.